2018
DOI: 10.7705/biomedica.v38i0.3728
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad genética de Aedes aegypti en el departamento de Sucre, Colombia, mediante el análisis de la secuencia de nucleótidos del gen mitocondrial ND4

Abstract: Introduction. Aedes aegypti is the most important mosquito species in America for the transmission of viruses of dengue, Zika, Chikungunya and yellow fever. Ecological factors as well as chemical controls can affect the genetic composition of Ae. aegypti populations, which is why its genetic characterization is necessary. Objective. To determine the genetic variability of Ae. aegypti populations in four municipalities of Sucre department, Colombia. Materials and methods. Larvae of Ae. aegypti, collected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…Microgeographic structure of Colombian populations has been slightly traced so far, but no clear picture of population demographic has been supported. Several studies at local level using dominant genetic markers such as RAPDs, (14) and nucleotide sequence analyses of mitochondrial genes, such as COI (17) and NADH dehydrogenase subunit 4 (ND4) (15,16) unveiled Colombian Ae. aegypti populations show moderated population differences at spatiotemporal scales, and it was suggested as a consequence of local pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microgeographic structure of Colombian populations has been slightly traced so far, but no clear picture of population demographic has been supported. Several studies at local level using dominant genetic markers such as RAPDs, (14) and nucleotide sequence analyses of mitochondrial genes, such as COI (17) and NADH dehydrogenase subunit 4 (ND4) (15,16) unveiled Colombian Ae. aegypti populations show moderated population differences at spatiotemporal scales, and it was suggested as a consequence of local pressures.…”
Section: Discussionmentioning
confidence: 99%
“…(11,12,13) In Colombia, a first study based on random amplified polymorphic DNA-polymerase chain reaction products analysis (RAPD) reported local genetic population substructure in city of Cali, which was suggested involved in differences of vector competence and insecticide resistance ratios. (14) Likewise, genetic analyses based on partial nucleotide sequences of mitochondrial NADH dehydrogenase 4 (ND4) gene, disclosed local microgeographic differences among individuals of municipalities of Sincelejo, Guaranda, Corozal and Sampués (within a maximum range of ~100 km) from Sucre department, (15,16) as well as from Medellin city. (17) These studies would suggest a complex heterogeneous population substructure is placed throughout Colombian populations mainly as consequence of local differences on selective pressures from the chemical control.…”
mentioning
confidence: 99%
“…The A. aegypti and A. albopictus classification of individuals is mainly determined by morphological identification (Kraemer et al, 2015), and few reports use molecular identification (Zamora-Delgado et al, 2015;Atencia et al, 2018). Although, morphological identification is the most widely used classification technique, it has different limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the genetic variation of Ae. aegypti populations in the neighboring countries, Perú (Costa-da-Silva et al 2005), Colombia (Jaimes-Dueñez et al 2015, Atencia et al 2018) and Brazil (Monteiro et al 2014, Paduan and Ribolla 2008). In Ecuador, there were two haplotypes, which show low genetic diversity in all the sampled localities, although the ecological differences among the geographical areas are apparent among the Pacific coast, Amazon basin and the Galápagos Islands.…”
Section: Discussionmentioning
confidence: 99%